Comparison of the evolutionary patterns of DNA repeats in ancient and young invertebrate species flocks of Lake Baikal - Wang Yuxiang; T. E. Peretolchina; E. V. Romanova; D. Y. Sherbakov (Вавиловский журнал генетики и селекции)
DNA repeat composition of low coverage (0.1–0.5) genomic libraries of four amphipods species endemic to Lake Baikal (East Siberia) and four endemic gastropod species of the fam. Baicaliidae have been compared to each other. In order to do so, a neighbor joining tree was inferred for each quartet of species (amphipods and mollusks) based on the ratio of repeat classes shared in each pair of species. The topology of this tree was compared to the phylogenies inferred for the same species from the concatenated protein-coding mitochondrial nucleotide sequences. In all species analyzed, the fraction of DNA repeats involved circa half of the genome. In relatively more ancient amphipods (most recent common ancestor, MRCA, existed approximately sixty millions years ago), the most abundant were species-specific repeats, while in much younger Baicaliidae (MRCA equal to ca. three millions years) most of the DNA repeats were shared among all four species. If the presence/absence of a repeat is regarded as a separate independent trait, and the ratio of shared to total numbers of repeats in a species pair is used as the measure of distance, the topology of the NJ tree is the same as the quartet phylogeny inferred for the mitogenomes protein coding nucleotide sequences. Meanwhile, in each group of species, a substantial number of repeats were detected pointing to the possibility of non-neutral evolution or a horizontal transfer between species occupying the same biotope. These repeats were shared by non-sister groups while being absent in the sister genomes. On the other hand, in such cases some traits of ecological significance were also shared.